Professors Andriy Pavlovich Vinogradov and Pavlo Terentiiovich Yemelyanenko and their role in the establishment and development of higher technical education in the Dniro region - Myronenko , M.A. (Theory and Practice of Metallurgy, 2025)
The establishment and development of higher technical education in the Dnipro region is a multifaceted phenomenon in which both objective and subjective factors are important. Undoubtedly, the role of socio-political processes and decisions made by state bodies is significant. However, the personality of a scientist working in a scientific or educational institution has no less influence on the course of events. This article, intended for a wide audience, presents information about two such scientists celebrating their anniversaries in 2025: Andrii Pavlovych Vinogradov and Pavlo Terentiiovych Yemelianenko.